2015
DOI: 10.5603/ep.a2016.0048
|View full text |Cite
|
Sign up to set email alerts
|

Rozpuszczalne białko α-Klotho — nowy marker aktywności akromegalii?

Abstract: Introduction: Klotho is a transmembrane protein that attenuates insulin/insulin-like growth factor-1 (IGF-1) signalling and appears to be involved in ageing. Recent data suggest that soluble a-Klotho (sKlotho) is also elevated in acromegaly. The aim of this study was to assess serum levels of sKlotho in patients in relation to the activity of the disease and to compare with the control group. Material and methods: We studied 55 patients with acromegaly and 29 healthy controls (CG). Patients were divided into t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…Normalization of sαKL was seen to the same extent in patients controlled by surgery alone or by surgery and SSA treatment. This is in line with preliminary data from a smaller study reporting a decrease in sαKL concentrations in patients who were biochemically controlled with octreotide after surgery ( 28 ). In contrast to normalization in controlled patients, sαKL remained elevated in all our patients who were defined as uncontrolled by GH random and IGF-I after surgery with or without SSA.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Normalization of sαKL was seen to the same extent in patients controlled by surgery alone or by surgery and SSA treatment. This is in line with preliminary data from a smaller study reporting a decrease in sαKL concentrations in patients who were biochemically controlled with octreotide after surgery ( 28 ). In contrast to normalization in controlled patients, sαKL remained elevated in all our patients who were defined as uncontrolled by GH random and IGF-I after surgery with or without SSA.…”
Section: Discussionsupporting
confidence: 91%
“…Since klotho was first described in the context of longevity ( 17 ), one might expect its concentrations would correlate with age ( 19 , 49 ). However, while a weak negative correlation has been reported by 1 study ( 34 ), many others could not confirm this ( 50 , 51 ) and reported similar sαKL concentrations throughout life ( 26 , 28 , 34 , 41 , 52-54 ). The few previous studies in patients with acromegaly also did not report a correlation between sαKL and age ( 28 , 55 ).…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…In active, but not in controlled acromegaly, high levels of sKlotho and FGF-23 have been reported compared to controls [173]. After remission, sKlotho levels rapidly normalized [173]. The potentially beneficial effects of the high sKlotho levels on endothelial function and inflammation seem to be outweighed by negative effects of hyperphosphataemia and other disturbances related to GH/ IGF-1 excess, and are insufficient to reverse the increased cardiovascular risk in acromegaly.…”
Section: Klothomentioning
confidence: 97%
“…Also in humans, lower sKlotho levels are associated with atherosclerosis and inflammation [226,229]. In active, but not in controlled acromegaly, high levels of sKlotho and FGF-23 have been reported compared to controls [173]. After remission, sKlotho levels rapidly normalized [173].…”
Section: Klothomentioning
confidence: 99%